2019
DOI: 10.3390/s19245458
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Thiophene-Based Fluorescent Chemosensor for the Detection of Zn2+ and CN−: Imaging Applications in Live Cells and Zebrafish

Abstract: A novel fluorescent turn-on chemosensor DHADC ((E)-3-((4-(diethylamino)-2hydroxybenzylidene)amino)-2,3-dihydrothiophene-2-carboxamide) has been developed and used to detect Zn 2+ and CN − . Compound DHADC displayed a notable fluorescence increase with Zn 2+ . The limit of detection (2.55 ± 0.05 µM) for zinc ion was far below the standard (76 µM) of the WHO (World Health Organization). In particular, compound DHADC could be applied to determine Zn 2+ in real samples, and to image Zn 2+ in both HeLa cells and ze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 57 publications
1
10
0
Order By: Relevance
“…S10A and S10B). These are comparable to the values reported for other chemosensors for Cu 2+ and Zn 2+ ions [64][65][66][67][68][69] and adequate to recognize Cu 2+ and Zn 2+ ions in biological systems [70,71].…”
Section: Metal Ion Sensing Studiessupporting
confidence: 88%
“…S10A and S10B). These are comparable to the values reported for other chemosensors for Cu 2+ and Zn 2+ ions [64][65][66][67][68][69] and adequate to recognize Cu 2+ and Zn 2+ ions in biological systems [70,71].…”
Section: Metal Ion Sensing Studiessupporting
confidence: 88%
“…Moreover, investigating the practical applications of the probe, it was observed that sensor 42 filter paper could detect CN − , which is evident by the color change from blue to yellow and the LOD was noted to be 0.89 µM [86], implying that the probe could be implemented for the detection of CN − ions. From the results, it was then confirmed that the probe [87] could be utilized for the selective detection of CN − by the fluorescent turn-on method in aqueous systems.…”
Section: Cyanidementioning
confidence: 75%
“…The LOD for CN − was 44.6 µM, and the detection process was proposed through H-NMR titrations, which showed that deprotonation of the probe could result in the ICT suppression, thereby inducing fluorescence ‘turn-on’ of probe 43 -H + ( Scheme 40 ) . From the results, it was then confirmed that the probe [ 87 ] could be utilized for the selective detection of CN − by the fluorescent turn-on method in aqueous systems.…”
Section: Thiophene Based Chemosensors For the Detection Of Anionsmentioning
confidence: 88%
“…The approaches for CN − detection, such as potentiometric and conventional titrations, are time‐consuming and require skillful handling. Therefore, a large number of selective sensors have been developed and provide convenient and rapid strategies for CN − detection [39–52] . The fluorescent chemical sensors exhibit many satisfactory characteristics such as high sensitivity and selectivity, visual detection and optical imaging [53–68] .…”
Section: Introductionmentioning
confidence: 99%